Management and Long-term Outcomes of Crohn's Disease Complicated with Enterocutaneous Fistula: ECUFIT Study from GETECCU. (1st February 2022) - Barreiro-de Acosta, Manuel; Riestra, Sabino; Calafat, Margalida; Soto, María Pilar; Calvo, Marta; Sánchez Rodríguez, Eugenia; Caballol, Berta; Vela, Milagros; Rivero, Montserrat; Muñoz, Fernando; de Castro, Luisa; Calvet, Xavier; et al.
Abstract: Background and aims: Crohn's disease [CD] can develop penetrating complications at any time during the disease course. Enterocutaneous fistulae [ECF] are disease-related complications with an important impact on quality of life. Our aim was to describe the outcomes of this complication, including its medical and/or surgical management and their temporal trends. The primary endpoint was fistula closure, defined as the absence of drainage, with no new abscess or surgery, over the preceding 6 months. Methods: Clinical information from all adult patients with CD and at least one ECF—excluding perianal fistulae—were identified from the prospectively-maintained ENEIDA registry. All additional information regarding treatment for this complication was retrospectively reviewed. Results: A total of 301 ECF in 286 patients [January 1970-September 2020] were analysed out of 30 088 records. These lesions were mostly located in the ileum [67%] and they had a median of one external opening [range 1-10]. After a median follow-up of 146 months (interquartile range [IQR], 69-233), 69% of patients underwent surgery. Fistula closure was achieved in 84%, mostly after surgery, and fistula recurrence was uncommon [13%]. Spontaneous and low-output fistulae were associated with higher closure rates (hazard ratio [HR] 1.51, 95% confidence interval [CI] 1.17-1.93, p  = 0.001, and HR 1.49, 95% CI 1.07-2.06, p  = 0.03, respectively); this was obtained more frequently with medical therapy since biologics have been available. Conclusions: ECF complicating CD are rare but entail a high burden of medical and surgical resources. Closure rates are high, usually after surgery, and fistula recurrence is uncommon. A significant proportion of patients receiving medical therapy can achieve fistula closure.